Green catalyst Fe(OTs)(3)/SiO2 for the synthesis of 4-Pyrrolo-12-oxoquinazolines - Allaka, Bhargava Sai; Basavoju, Srinivas; Krishna, Gamidi Rama (ChemistrySelect, 2020)
An efficient and eco-friendly diversity-oriented synthetic protocol has been presented to synthesize structurally versatile drug-like molecules under solvent-free grinding in the presence of Fe(OTs)(3)/SiO2 as a catalyst. The use of Fe(OTs)(3)/SiO2 as a recyclable and reusable catalyst has been explored in the synthetic domino protocol involving one-pot, three component reaction for the synthesis of 4-pyrrolo-12-oxoquinazolines with special features of the protocol like high atom-economy, operational simplicity, short reaction time and high selectivity with excellent yields.
Keywords: 4-Pyrrolo-12-oxoquinazolines; Fe(OTs)(3); Green methodology; Liquid Assisted Grinding (LAG); SiO2 catalyst; Solvent-free grinding

Transition metal- and oxidant-free regioselective synthesis of 3,4,5-trisubstituted pyrazoles by means of [3+2] cycloaddition reactions - Allaka, Bhargava Sai; Basavoju, Srinivas; Gamidi, Rama Krishna (ChemistrySelect, 2022)
A highly efficient regioselective synthesis of 3,4,5-trisubstituted pyrazoles via transition metal- and oxidant-free, three component [3+2] cycloaddition with thiazolidinedione chalcones, benzaldehydes and N-tosylhydrazine is described. The reaction proceeds through C-C and C-N bond formations under mild reaction conditions to produce structurally diverse polysubstituted pyrazoles in moderate to good yields.
Keywords: 3; 4; 5-trisubstituted pyrazoles; Cycloaddition; Multicomponent reaction; Oxidant free; Regioselectivity; Transition metal free

Design and synthesis of novel quinazolinyl-bisspirooxindoles as potent anti-tubercular agents: an ultrasound-promoted methodology - Allaka, Bhargava Sai; Basavoju, Srinivas; Rekha, Estharla Madhu; Sriram, Dharmarajan; Krishna, Gamidi Rama (Molecular Diversity, 2023)
The essential need for the potent anti-tubercular (anti-TB) agents with high selectivity and safety profile prompted us to synthesize a new series of quinazolinyl-bisspirooxindoles. The title compounds were synthesized by one-pot multicomponent [3 +2] cycloaddition reaction under ultrasonication. Further, in vitro anti-TB activity was evaluated against Mycobacterium tuberculosis H37Rv. Among the screened compounds, two compounds (4q and 4x) showed potent activity with MIC value 1.56 mu g/mL and four compounds exhibited significant activity (MIC =3.125 mu g/mL), and also cytotoxicity studies against RAW 264.7 cell lines reveal that most active compounds were less toxic to humans. In addition, in order to demonstrate the inhibitory properties, molecular docking studies were carried out and the results showed that the target compounds have good binding energy and better binding affinity within the active pocket, thus these compounds may consider to be as potent inhibitors toward selective targets.
Keywords: anti-tubercular activity; bisspirooxindoles; Cytotoxicity screening; Molecular docking studies; ultrasonication

Ultrasound assisted green protocol for the synthesis of quinoxaline based bisspirooxindoles: crystal structure analysis, enone umpolung, DFT calculations, anti-cancer activity, and molecular docking studies - Baddepuri, Sravanthi; Allaka, Bhargava Sai; Gamidi, Rama Krishna; Faizan, Mohmmad; Pawar, Ravinder; Basavoju, Srinivas (Synthetic Communications, 2023)
A series of novel quinoxaline based bisspirooxindolo-pyrrolizidines were synthesized through 1,3-dipolar cycloaddition under ultrasonication with shorter reaction time and good yields. The compounds were well characterized by various spectroscopic methods and finally single crystal X-ray diffraction method (4c, 4d). DFT energy calculations confirm the regioselectivity due to enone umpolung effect. The in vitro anti-cancer activity of the synthesized compounds (4a-s) shows that the compounds 4g and 4q exhibited good anti-cancer activity with IC50 values14.51 +/- 1.1 and 11.36 +/- 0.23 mu M against DU-145 prostate cancer cell line; and 16.78 +/- 0.95 and 14.28 +/- 0.64 mu M against Hela cervical cancer cell lines when compared to the standard anti-cancer drug doxorubicin (1.75 +/- 0.06 and 1.35 +/- 0.09 mu M). In silico molecular docking studies indicated that the synthesized compounds may serve as a potential lead for the further development of novel anti-cancer agents.
Keywords: Anti-cancer activity; bisspirooxindoles; DFT calculations; Hirshfeld surface; ultrasonication

Ultrasound assisted synthesis of spirooxindolo-1,2,4-oxadiazoles via [3+2] cycloaddition reaction and their anti-cancer activity - Kanchrana, Madhu; Allaka, Bhargava Sai; Krishna, Gamidi Rama; Basavoju, Srinivas (ARKIVOC, 2023)

Synthesis of quinazolinone based spirocyclopropanes via [3?+?2] cycloaddition reaction: in silico anti-tubercular molecular docking studies and ADME prediction - Allaka, Bhargava Sai; Kanchrana, Madhu; Gamidi, Rama Krishna; Basavoju, Srinivas (Polycyclic Aromatic Compounds, 2024)
A highly efficient cascade annulation approach is developed for the synthesis of novel quinazolinone-based spirocyclopropanes via three-component [3 + 2] cycloaddition reaction with aldehydes, tosylhydrazide and quinazolinyl chalcones. The reaction features the formation of two C–C bonds and three stereogenic centers. A variety of highly functionalized spirocyclopropyl quinazolinones were obtained in good yields under mild reaction conditions. Furthermore, in silico anti-tubercular (anti-TB) molecular docking studies were performed for the generated compounds against three Mycobacterium tuberculosis proteins with PDBID: 1DF7, 1P44 and 4TZK. ADME prediction were evaluated for the drug like properties of the synthesized compounds.